Factors Influencing Students’ Choice of Bachelor of Hotel Management Program in Nepal - Shrestha, Richan; Bhattarai, Prakash Chandra (Journal of Training and Development, 2026)
The choice of academic programs for higher education is a crucial decision after school for students. It is one of the difficult decisions they make as they face dilemmas for choosing a right program which is influenced by different factors. Similar is the case with Bachelor of Hotel Management (BHM) students. Remarkably, little is known about the reasons behind the BHM choice in Nepal. With this consideration, a survey was conducted among 251 Bachelor of Hotel Management students in Kathmandu, Nepal. For this, exploratory factor analysis was used for data analysis. The result revealed four components: i) self-interest, ii) career development perception, iii) outcome expectations, and iv) social pressure. The findings of this study can help students and their parents to understand dimensions of BHM choice. The result can also benefit hotel management schools to counsel the students during the admission process.